An electrocrystallization preparation method of titanium niobate material with entropy reduction characteristics and its application

Through the electrochemical-driven entropy reduction strategy, low-temperature anodization method, the preparation and lithiation of titanium niobate material was solved, and the problems of low lithium-ion electrode materials were optimized and the battery performance was achieved. Improvement.

CN118516684BActive Publication Date: 2025-02-14XIAN JINSHAJIANG ELECTRONICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410639607.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-22
Publication Date
2025-02-14
Estimated Expiration
2044-05-22

AI Technical Summary

Technical Problem

The lithium-ion battery negative electrode material graphite has a low lithium-ion battery potential, which is prone to lithium dendrites, causing battery failure and even causing fires. In addition, the electronic and ionic conductivity of titanium niobate materials is low under conventional preparation processes, which affects its cycle life. and specific capacity.

Method used

The titanium niobate material was prepared by electrochemically driven entropy reduction strategy by low-temperature anodization method, and then lithiated to convert it into a crystalline structure of the rock salt phase to improve the structural order and ionic conductivity of the material.

Benefits of technology

It significantly improves the cycling performance and rate performance of titanium niobate materials, extends the cycle life of the battery, improves the discharge specific capacity and energy utilization efficiency, and reduces the preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118516684B_ABST
    Figure CN118516684B_ABST
Patent Text Reader

Abstract

A method for preparing an electrocrystallization titanium niobate material with entropy reduction characteristics and its application, belonging to the field of secondary batteries, the specific scheme is as follows: preparing a niobium-titanium alloy foil; preparing porous amorphous titanium niobate by an anodic oxidation process, and transforming it into a crystalline titanium niobate material after undergoing a lithiation cycle. The preparation method of the present invention is simple, low-cost, and has low equipment requirements. The present invention prepares an entropy-reduced titanium niobate material for the first time and applies it to the negative electrode material of a lithium-ion battery. The structural order of the titanium niobate after the lithiation cycle is highly increased, which reduces the tortuosity of the lithium ion transmission channel inside the solid, which is beneficial to the rapid transmission of lithium ions, thereby improving the ionic conductivity and the stability of the crystal structure, so that the titanium niobate material exhibits excellent electrochemical properties when used as a negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of secondary batteries, and specifically relates to an electrocrystallization preparation method of titanium niobate material based on an electrochemically driven entropy reduction strategy and its application in secondary batteries. Background Art

[0002] As an important component of the new generation of energy storage devices, lithium-ion batteries are known for their high energy density, high voltage, wide operating temperature range and long storage life. In the military and civilian fields, lithium-ion batteries have become one of the first choices for energy storage appliances. Whether it is used for long-term stable power supply of military equipment or for efficient energy for portable electronic devices, lithium-ion batteries have demonstrated their excellent performance and reliability.

[0003] Graphite is a commonly used negative electrode material for commercial secondary batteries, but graphite has a low lithium deposition potential and is very prone to producing lithium dendrites, which can lead to battery failure and even fire, thermal runaway, etc. Therefore, it is necessary to find a lithium-ion battery negative electrode material with high lithium deposition potential, low dendrite production, good safety and large capacity.

[0004] In recent years, titanium niobate has attracted much attention as a low-temperature, high-capacity negative electrode material for lithium-ion batteries, and is expected to replace lithium titanate. As a negative electrode material, titanium niobate (TiNb2O7, NTO) has shown unique advantages in high power, intrinsic safety and long life, providing new possibilities for improving the high-power charging and discharging performance and expanding the application of lithium-ion batteries. Titanium niobate not only has the advantages of conventional lithium titanium materials in terms of cycle stability and long life, but also has the advantages of Ti 3+ / Ti 4+ , Nb 4+ / Nb 5+ and Nb 3+ / Nb 4+ Multiple redox pairs, with higher theoretical specific capacity (387.6 mAh g -1 , much higher than lithium titanate, and even higher than graphite negative electrode), and the working potential is similar to that of lithium titanate (1.6V vs Li + / Li), which can effectively prevent the generation of lithium dendrites and the reduction and decomposition of the electrolyte. Compared with traditional batteries, the cycle life is greatly improved. However, titanium niobate also has serious problems. Since the material has a variety of different crystal forms, the electronic and ionic conductivity of the material obtained under conventional preparation conditions is low. Therefore, it is urgent to develop a new preparation process to achieve a long-life, high-energy-density lithium-ion battery titanium niobate negative electrode material through a simple preparation method. Summary of the invention

[0005] Based on the above technical background, the present invention provides an electrocrystallization preparation method of titanium niobate material developed based on an electrochemically driven entropy reduction strategy and its application in the negative electrode of a long-life lithium-ion battery, aiming to optimize the crystal structure of the titanium niobate material through a simple process, improve the electronic and ionic conductivity of the material, achieve a significant improvement in the long cycle performance of the negative electrode material for lithium-ion batteries and a high degree of optimization of the rate performance, and provide a new technical breakthrough for the titanium niobate negative electrode material to fully exert its lithium storage performance.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing a titanium niobate material having entropy reduction characteristics by electrocrystallization comprises the following steps:

[0008] Step 1: cooling a mixture of molten niobium and titanium to obtain a niobium-titanium alloy foil, wherein the molar ratio of niobium to titanium is 1:2-1:4; or melting titanium tetrachloride and niobium pentachloride at a molar ratio of 3:1-6:1 to obtain a mixture, placing an inert platinum electrode therein and applying electricity, and electrolyzing the mixture to obtain a niobium-titanium alloy foil;

[0009] Step 2: Using the niobium-titanium alloy foil as an anode and the inert electrode lead plate as a cathode, an anodic oxidation reaction occurs in an anodic oxidation electrolyte to obtain amorphous titanium niobate;

[0010] Step 3: Use amorphous titanium niobate as the positive electrode material and lithium foil as the negative electrode, assemble the battery with commercial electrolyte, perform charge and discharge cycles, and disassemble to obtain crystallized titanium niobate material.

[0011] Furthermore, in step 1, the metal niobium and the metal titanium are melted in a hydrogen and argon atmosphere and then uniformly mixed, or the metal niobium powder and the metal titanium powder are mixed and then melted at a high temperature in a hydrogen and argon atmosphere. The melting temperature is 1500° C. and the time is 4 hours.

[0012] Furthermore, in step 2, the anodic oxidation electrolyte includes a strong oxidant, a strong acid and deionized water, wherein the mass fraction of the strong oxidant in the anodic oxidation electrolyte is 10%-20%, preferably 13%, and the mass fraction of the strong acid in the anodic oxidation electrolyte is 20%-30%. The strong oxidant is used to provide an oxidizing environment for the oxidation process of the niobium-titanium alloy, and the strong acid is used to maintain the electrolyte at a low pH value to enhance the oxidizing property of the oxidant.

[0013] Furthermore, the strong oxidant includes one or a combination of chromic anhydride and potassium permanganate, and the strong acid includes one or a combination of sulfuric acid and nitric acid.

[0014] Furthermore, in step 2, the temperature of the anodic oxidation reaction is 40-60°C, preferably 45°C, and the current density is 20Adm-2 , the electrolysis time is 45min.

[0015] Furthermore, in step three, the electrolyte used to assemble the battery is a commercial electrolyte, which includes LiPF6 and EC, DEC and DMC in a molar ratio of 1:1:1, wherein the molar concentration of LiPF6 is 1 mol / L.

[0016] Furthermore, in step three, the thickness of the metal lithium foil is 1 mm and the diameter is 16 mm.

[0017] Furthermore, in step 3, the voltage range of the charge-discharge cycle is 0.2-3.0 V, and the current density is set to 1 mA cm -2 , the number of cycles is 10-50.

[0018] Preferably, the strong oxidant is chromic anhydride, the strong acid is sulfuric acid, and the formula of the anodizing electrolyte is: chromic anhydride is 200g, sulfuric acid is 300g, and deionized water is 1000g.

[0019] Furthermore, in step 1, titanium tetrachloride and niobium pentachloride are melted at 230°C in an inert atmosphere, and a current density of 3-10 Adm is passed through an inert platinum electrode. -2 .

[0020] An application of the titanium niobate material with entropy reduction characteristics prepared by the preparation method, wherein the titanium niobate material with entropy reduction characteristics is applied as a negative electrode material for a lithium ion battery.

[0021] Furthermore, the titanium niobate material with entropy reduction characteristics is dispersed in a solvent as a negative electrode active material with a conductive agent and a binder to obtain a negative electrode slurry, and the negative electrode slurry is coated on a negative electrode collector, and a negative electrode sheet is obtained through drying, rolling and punching.

[0022] Furthermore, the binder is polyvinylidene fluoride (PVDF), the conductive agent is acetylene black, and the solvent is N-methylpyrrolidone (NMP). The mass ratio of the negative electrode active material: the conductive agent: the binder is 80%: 10%: 10%.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1) In the present invention, the titanium niobate material obtained by low-temperature anodic oxidation is a high-entropy amorphous state. The titanium niobate material obtained under this condition has a complex structure, a high degree of tortuosity of the ion transmission path inside the solid phase, and a large resistance to lithium ion conduction; the amorphous lithium niobate material is subjected to lithiation treatment, and the periodic insertion / extraction of lithium ions driven by the electrochemical potential can catalyze the transformation of the titanium niobate electrode into a rock salt phase crystalline structure, and the structural order of titanium niobate is greatly increased, which reduces the tortuosity of the lithium ion transmission channel inside the solid, which is conducive to the rapid transmission of lithium ions, thereby improving the ion conductivity; the lithiation process will leave structural lithium elements inside the titanium niobate material, so that the internal lithium ion transmission channel of the titanium niobate material prepared by the electrocrystallization method is smoother during the charge and discharge cycle, and the stability of the crystal structure is greatly improved. Compared with the titanium niobate material prepared by the conventional high-temperature solid phase synthesis method, the entropy-reduced titanium niobate material used for the lithium battery negative electrode has a longer cycle life and a higher discharge specific capacity, and has a higher energy utilization efficiency than the conventional high-temperature solid phase synthesized titanium niobate material.

[0025] 2) The preparation method of the present invention is simple, low-cost, has low requirements on equipment, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The XRD spectrum of the entropy-reduced titanium niobate material synthesized by the present invention;

[0027] Figure 2 This is a 0.2C rate long cycle charge and discharge test diagram of the entropy-reduced titanium niobate material and the titanium niobate material synthesized by the conventional high-temperature solid phase method;

[0028] Figure 3 This is a comparison chart of the charge and discharge performance of entropy-reduced titanium niobate material and titanium niobate material synthesized by conventional high-temperature solid-phase method under 9 different rate conditions at room temperature. DETAILED DESCRIPTION

[0029] The technical solution of the present invention will be clearly and completely described below in conjunction with the drawings and embodiments. Obviously, the described embodiments are only part of the embodiments of the invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0030] Example 1

[0031] A method for preparing a titanium niobate material having entropy reduction characteristics by electrocrystallization comprises the following steps:

[0032] Step 1: uniformly mix metal niobium powder and titanium powder in a molar ratio of 1:4, then melt and calcine them at 1500°C for 4 hours in a hydrogen and argon atmosphere tube furnace, and then cool them to obtain niobium-titanium alloy foil.

[0033] Step 2: Using niobium-titanium alloy foil as anode and lead plate as cathode, anodizing reaction is carried out in an anodic oxidation electrolyte composed of 200g chromic anhydride, 300g sulfuric acid and 1000g deionized water to obtain amorphous titanium niobate foil. The reaction conditions are: reaction temperature 45°C, current density 20Adm -2 , electrolysis time is 45min;

[0034] Step 3: Finally, amorphous titanium niobate is used as the positive electrode active material, a conductive agent and a binder are added, and the positive electrode is prepared according to the conventional method. Metal lithium is used as the negative electrode and a commercial electrolyte is used to assemble the battery. 20 charge and discharge cycles are performed in the range of 0.2-3.0V at room temperature to obtain the crystalline titanium niobate material after lithium cycle.

[0035] Example 2

[0036] The entropy-reduced titanium niobate material obtained in Example 1 is used as a negative electrode material for lithium-ion batteries. The negative electrode slurry includes 80% by mass of the entropy-reduced titanium niobate material, 10% of the conductive agent and 10% of the binder.

[0037] Figure 1 This is the XRD spectrum of electrocrystallized titanium niobate material. It can be seen that the material now has characteristic peaks of oxide structure, indicating that the material has achieved the transition from amorphous to crystalline state and completed the entropy reduction process. Figure 2 It can be seen that in the 0.2C long cycle test, the discharge specific capacity performance of the entropy-reduced titanium niobate material obtained in this embodiment is still maintained at 275 mAh g after 500 cycles. -1 The capacity retention rate is over 95%; this performance is better than that of titanium niobate material synthesized by conventional high-temperature solid phase process (the specific capacity is 220mAh g after 500 cycles). -1 , capacity retention rate is close to 80%). Figure 3 The nine rate performance test graphs also show the excellent discharge specific capacity and electrochemical stability of the material: in 50 cycles at the same rate, the conventional high-temperature solid-phase synthesized titanium niobate material showed a significant decrease in specific capacity, while the entropy-reduced titanium niobate material showed almost no decrease in specific capacity; and at extremely high rate conditions of 50C and 100C, the specific capacity of the entropy-reduced titanium niobate material exceeded that of the conventional material by nearly 30 mAh g -1 The excellent performance of entropy-reduced titanium niobate is due to the structural transformation of the electrode material from disorder to order in the microstructure, which greatly reduces the tortuosity of the lithium ion conduction path and improves the ion transfer kinetics, making the entropy-reduced titanium niobate material exhibit excellent electrochemical properties, and obtain a sufficiently long cycle life and higher high-rate discharge performance.

[0038] Example 3

[0039] The entropy-reduced titanium niobate material prepared in this embodiment is different from that in embodiment 1 in that the process for obtaining the niobium-titanium alloy foil is changed from high-temperature smelting to electrolytic reduction, titanium tetrachloride and niobium pentachloride in a molar ratio of 3:1 are mixed in an inert atmosphere and then heated and melted with a resistance wire at 230°C to obtain a mixture, an inert metal platinum is used as an anode and placed in the mixture, and a current density of 5Adm is passed through the inert metal platinum. -2 The niobium-titanium alloy foil is obtained by electrolysis with an electric current of , and this method is conducive to reducing the industrial production cost.

[0040] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing titanium niobate material with entropy reduction characteristics by electrocrystallization, characterized in that: The following steps are involved: Step 1: cooling a mixture of molten niobium and titanium to obtain a niobium-titanium alloy foil, wherein the molar ratio of niobium to titanium is 1:2-1:4; or melting titanium tetrachloride and niobium pentachloride at a molar ratio of 3:1-6:1 to obtain a mixture, placing an inert electrode therein and applying power, and electrolyzing the mixture to obtain a niobium-titanium alloy foil; Step 2: Using the niobium-titanium alloy foil as an anode and the inert electrode as a cathode, an anodic oxidation reaction occurs in an anodic oxidation electrolyte to obtain amorphous titanium niobate; the anodic oxidation electrolyte comprises a strong oxidant, a strong acid and deionized water, the mass fraction of the strong oxidant in the anodic oxidation electrolyte is 10%-20%, and the mass fraction of the strong acid in the anodic oxidation electrolyte is 20%-30%; the strong oxidant comprises one or a combination of two of chromic anhydride and potassium permanganate, and the strong acid comprises one or a combination of two of sulfuric acid and nitric acid; Step 3: Use amorphous titanium niobate as the positive electrode material and lithium foil as the negative electrode, assemble the battery, perform charge and discharge cycles, and disassemble to obtain crystallized titanium niobate material.

2. The preparation method according to claim 1, characterized in that: In step 2, the temperature of the anodic oxidation reaction is 40-60°C and the current density is 20 A dm -2 , the electrolysis time is 45 min.

3. The preparation method according to claim 1, characterized in that: In step 3, the electrolyte used in assembling the battery is a commercial electrolyte.

4. The preparation method according to claim 1, characterized in that: In step 3, the voltage range of the charge-discharge cycle was 0.2–3.0 V, and the current density was set to 1 mA cm -2 , the number of cycles is 10-50.

5. The preparation method according to claim 1, characterized in that: The strong oxidant is chromic anhydride, the strong acid is sulfuric acid, and the formula of the anodizing electrolyte is: chromic anhydride is 200 g, sulfuric acid is 300 g, and deionized water is 1000 g.

6. The preparation method according to claim 1, characterized in that: In step 1, titanium tetrachloride and niobium pentachloride are melted at 230°C in an inert atmosphere, and a current density of 3-10 A dm is passed through the inert electrode. -2 .

7. An application of a titanium niobate material having entropy reduction properties prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The titanium niobate material with entropy reduction characteristics is used as a negative electrode material for lithium-ion batteries.

8. The use according to claim 7, characterized in that: The titanium niobate material with entropy reduction characteristics is dispersed in a solvent as a negative electrode active material with a conductive agent and a binder to obtain a negative electrode slurry, and the negative electrode slurry is coated on a negative electrode current collector, and a negative electrode sheet is obtained through drying, rolling and punching.

Citation Information

Patent Citations

  • Modified clay compounded porous titanium lithium niobate battery negative electrode material and preparation method thereof

    CN108493408A

  • Mixed-phase niobium-titanium oxide as well as preparation method and energy storage application thereof

    CN113772728A